Paenibacillus lutrae sp. nov., A Chitinolytic Species Isolated from A River Otter in Castril Natural Park, Granada, Spain - Rodriguez, Miguel; Reina, José Carlos; Béjar, Victoria; Llamas, Inmaculada (MDPI, 2019)
A highly chitinolytic facultative anaerobic, chemoheterotrophic, endospore-forming, Gram-stain-positive, rod-shaped bacterial strain N10T was isolated from the feces of a river otter in the Castril Natural Park (Granada, Spain). It is a slightly halophilic, motile, catalase-, oxidase-, ACC deaminase- and C4 and C8 lipase-positive strain. It is aerobic, respiratory and has a fermentative metabolism using oxygen as an electron acceptor, produces acids from glucose and can fix nitrogen. Phylogenetic analysis of the 16S rRNA gene sequence, multilocus sequence analysis (MLSA) of 16S rRNA, gyrB, recA and rpoB, as well as phylogenomic analyses indicate that strain N10T is a novel species of the genus Paenibacillus, with the highest 16S rRNA sequence similarity (95.4%) to P. chitinolyticus LMG 18047T and <95% similarity to other species of the genus Paenibacillus. Digital DNA–DNA hybridization (dDDH) and average nucleotide identity (ANIb) were 21.1% and <75%, respectively. Its major cellular fatty acids were anteiso-C15:0, C16:0, and iso-C15:0. G + C content ranged between 45%–50%. Using 16S rRNA phylogenetic and in silico phylogenomic analyses, together with chemotaxonomic and phenotypic data, we demonstrate that type strain N10T (= CECT 9541T =LMG 30535T) is a novel species of genus Paenibacillus and the name Paenibacillus lutrae sp. nov. is proposed.
Keywords: Fungicidas; Paenibacillus lutrae; River otter; New species; Chitinolytic activity